UPAYA MENGEMBANGKAN KEMAMPUAN MOTORIK ANAK PRASEKOLAH - - Yudanto (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2006)
Kid which is in pre-school age is kid who is included in the age range of 2-6 years old. Inthese ages kids are in growth and development period. Pre-school period is an appropriatetime to develop all of the development aspects. Metrical ability is one of the important aspectsto be developed because it will highly determine their success in the future in doing physicalexercise tasks. In an educational surrounding, especially pre-school education, it is the dutyand assignment of the physical education teachers in developing kid’s metrical ability. Thereare various way to develop metrical ability of pre-school kids, those are : 1. increasing nutrientstatus of the kids, 2. improving playing activity of the kids, 3. improving physical fitness of thekids generally. Those efforts must be arranged in accordance with the growth and developmentstages of the kids, so that the results it achieves are fit with the hope it intends.Keywords : Effort, Metrical Ability, Pre-School Aged Kids.